Ligand field model for (C2v) metallocene complexesd3 and d4 strong-field energy matrices - Fiedler, Josef; Pavlík, Ivan; Pavlišta, Martin (Univerzita Pardubice, 2002)
Strong-field energy matrices expressed in terms of four d-orbital splitting parametrs (Ds, Dt, Dq, Dr) and two Racah parameteters (B, C) without spin-orbit coupling effects were calculated for the d3 and d4 (C2v) metallocene derivates.
Keywords: Metalloceny; komplexy; ligandy; modelové komplexy; chrom; molybden